Penyuluhan Bahaya Narkoba dan Miras Bagi Generasi Muda Di Kabupaten Muna - Trisnawati, Ira; Aminudin, Aminudin Aminudin; Mansabdar Kanande, La Ode (INSANIYAH, 2024)
The purpose of the counseling activity on the dangers of drugs and alcohol at Madrasah Aliyah Negeri (MAN) 1 Muna is to help participants understand the impacts of drug use, both physically, psychologically, and socio-economically. The socialization activity employs participatory methods, lectures, and discussions. It was conducted on March 1, 2024, with 40 students and 5 teachers participating in the event held at the MAN 1 Muna auditorium.This program aims to enhance the understanding of MAN 1 Muna students regarding the types of drugs and alcoholic beverages, the impacts of drug and alcohol abuse from physical, psychological, educational, social, and economic perspectives, as well as the prevention and mitigation strategies against drug and alcohol abuse among children and adolescents. Consequently, this socialization activity is expected to fortify the younger generation, particularly the students of MAN 1 Muna, as the nation's successors against the dangers of drug and alcohol abuse.Keywords : Counseling on the Dangers of Drugs and Alcohol, Young Generation